Circulating autotaxin levels in healthy teenagers: Data from the Vitados cohort - Méaux, Marie-Noëlle; Regnier, Maitena; Portefaix, Aurélie; Borel, Olivier; Alioli, Candide; Peyruchaud, Olivier; Legrand, Mélanie; Bacchetta, Justine (Frontiers in Pediatrics, 2023)
Autotaxin (ATX) is a secreted enzyme with a lysophospholipase D activity, mainly secreted by adipocytes and widely expressed. Its major function is to convert lysophosphatidylcholine (LPC) into lysophosphatidic acid (LPA), an essential bioactive lipid involved in multiple cell processes. The ATX-LPA axis is more and more studied because of its involvement in numerous pathological conditions, and more especially in inflammatory or neoplastic diseases, and in obesity. Circulating ATX levels gradually increase with the stage of some pathologies, such as liver fibrosis, thus being a potential interesting non-invasive marker for fibrosis estimation. Normal circulating levels of ATX have been established in healthy adults, but no data exist at the pediatric age. The aim of our study is to describe physiological concentrations of circulating ATX levels in healthy teenagers through a secondary analysis of the VITADOS cohort. In our study, ATX median levels were 1049 (450 – 2201) ng/mL. There was no difference in ATX levels between men and women teenagers, contrary to the gender difference described in adult population. ATX levels significantly decreased with age and pubertal status, reaching adult levels at the end of puberty. Our study also suggested positive correlations between ATX levels and blood pressure (BP), lipid metabolism and bone biomarkers. However, except for LDL cholesterol, these factors were also significantly correlated with age, which might be a confounding factor. Still, a correlation between ATX and diastolic BP has also been described in obese adult patients. No correlation was found between ATX levels and inflammatory marker C-reactive protein (CRP), Body Mass Index (BMI) and biomarkers of phosphate/calcium metabolism. In conclusion, our study is the first to describe the decline in ATX levels with puberty, and the physiological concentrations of ATX levels in healthy teenagers. This will be of upmost importance when performing clinical studies in children with chronic diseases to keep this kinetics in mind, as circulating ATX might become a non-invasive prognostic biomarker in pediatric chronic diseases.